The influence of firm charteristice on the level of CSR disclosure of the food processing companies in Malaysia - utilizing halal certification as moderating variable - Lestyo Sasono Wijito (2014)
There are previous studies examining the relationship between firm characteristics and the level of CSR disclosure, but the results are inconclusive. Limitations of the previous studies are: (i) they examine the level of total CSR disclosure instead of each type of CSR disclosure and (ii) they use general reporting frameworks rather than those intended for specific industry. This study makes efforts to deal with the limitations of previous studies by (i) examining the influence of firm characteristics (firm size, firm age, leverage, audit firm and profitability) on the level of each type of CSR disclosure such as food processing sector disclosure (FPSD), environmental disclosure (ENVD), and social disclosures (SOCD) within specific food processing companies and (ii) applying a disclosure index which is derived from the Food processing Sector Supplement (FPSS) of the GRI guidelines. Further, Halal certification is utilized to moderate the influence of firm characteristics on the level of FPSD, ENVD, and SOCD. The population of this study is the 2011 annual reports of 43 food processing companies listed in Bursa Malaysia. Partial Least Square (PLS) is applied to carry out the regression analysis. The results of this study show that, on average, the percentage number of Halal certified companies providing FPSD, ENVD, and SOCD is lower than those of Not Halal certified companies. They also reveal that firm size positively influences the level of ENVD and SOCD; firm age positively influences the level of SOCD; and leverage positively influences the level of FPSD, ENVD and SOCD. However, Halal certification only appears to reduce the positive influence of leverage on the level of ENVD and SOCD. This study might be useful for managers of the food processing companies to choose their disclosure strategy as well as give insights towards the legitimizing effect of Halal certification.